Monolayers of thiols with very high dipole moments show surprisingly small work function changes - Gärtner, Michael; Zharnikov, Michael; Terfort, Andreas (The journal of physical chemistry. C, Energy, materials, and catalysis, 2025)
A recently introduced concept of distributed dipoles in molecular self-assembly was combined with the standard dipolar tail group decoration in the context of the electrostatic engineering of surfaces and interfaces by self-assembled monolayers (SAMs). To this end, thiol-anchored molecules, containing dipolar 2,5′-bipyrimidine units within their molecular backbones, were decorated with either nitrile or dimethylamino tail groups and assembled on Au(111). The directions of the distributed and tail group dipoles were aligned either upward or downward to the anchor to achieve the maximum effect on the work function (WF) of the substrate. The SAMs were characterized by several complementary spectroscopic tools, with the data suggesting a dense molecular packing, a high degree of orientational order with only slight molecular inclination, and thiolate-gold anchoring for most of the molecules. At the same time, it turned out that the decoration of the bipyrimidine thiols with the tail groups not only provided no WF gain but even had a detrimental effect in the dimethylamino case. The most likely explanation for this outcome, based on the analysis of the available data, is the upside-down orientation of a part of the molecules in the SAMs, corresponding to their flip by 180° with respect to the standard thiolate anchoring configuration. The driving force of such a flip is the minimization of the energy associated with the strong dipole-dipole interaction between the SAM-forming molecules. Although being negative, this result can help in further rational design of functional molecules for WF adjustment, which is an important issue in organic electronics and photovoltaics.
Gesehen am 17.02.2026